2015
DOI: 10.3109/14992027.2014.986690
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective audiological analysis of bone conduction versus round window vibratory stimulation in patients with mixed hearing loss

Abstract: Analysis of the main cohort (n = 48) showed that treatment with round window vibroplasty leads to better hearing performance than treatment with a bone-anchored hearing device, if the bone conduction pure-tone average (0.5 to 4 kHz) is poorer than 35 dB HL. Audiological analysis in the smaller comparative analysis showed similar findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…A survival analysis will be conducted based on surgical questionnaires to map out potential complications that may arise, the associated time course and frequency of occurrence. Other measures to be compared to the literature will be patient satisfaction, benefit and quality of life [ 4 , 7 , 18 ], soundfield hearing thresholds [ 2 , 4 , 11 ] and speech perception [ 2 , 4 , 11 ]. Changes in surgical practice that have occurred over time will be considered in the review to determine the impact that these may have had on performance.…”
Section: Discussionmentioning
confidence: 99%
“…A survival analysis will be conducted based on surgical questionnaires to map out potential complications that may arise, the associated time course and frequency of occurrence. Other measures to be compared to the literature will be patient satisfaction, benefit and quality of life [ 4 , 7 , 18 ], soundfield hearing thresholds [ 2 , 4 , 11 ] and speech perception [ 2 , 4 , 11 ]. Changes in surgical practice that have occurred over time will be considered in the review to determine the impact that these may have had on performance.…”
Section: Discussionmentioning
confidence: 99%
“…Atas et al (24) presented quality-of-life questionnaire results on the same group of patients, with the subjects reporting statistically significant satisfaction with their AMEI. Mojallal et al (25) compared postoperative audiological data of patients with bone conduction devices to those implanted with the AMEI at the RW, and found that the AMEI-RW treatment delivered better results when the preoperative BC thresholds were closer to the range of 35 to 50 dB HL.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Treatment with round window vibroplasty leads to better hearing performance than treatment with a bone-anchored hearing device, if the bone conduction puretone average (0.5-4 kHz) is poorer than 35 dB HL. 34 A Jahrsdoerfer score of 4 or higher is recommended to consider a patient for implantation of an active middle ear implant and at least the round window should be accessible. 2 There have been successful implantations reported 35 for patients with Jahrsdoerfer score 3.…”
Section: Active Middle Ear Implantsmentioning
confidence: 99%